Capsule Endoscopy in Celiac Disease - E. Akin; O. Ersoy (Gastroenterology Research and Practice)
Capsule endoscopy (CE) has been increasingly used for diagnosing disease of the small bowel. It is an attractive technique for assessing celiac disease (CD) because it is noninvasive and provides a close and magnified view of the mucosa of the entire small bowel. The aim of this paper is to update the current data on the use of CE for diagnosing villous atrophy and complications of CD.